Comitentes y mecenas en la transición al Renacimiento: el Cabildo catedralicio leonés - Tejeira Pablos, María Dolores (Estudios humanísticos. Geografía, historia y arte, 1992)
The Church, specially the cathedral chapter, was the main patron in the kingdom of Castille in the transitional period to Renaissance. They were not only patrons with a certain artistic preferente, but the creators of a work relationship that will make the artist's way of life and work better.